Studying Aura in Hafiz’ Poetry Based on New Criticism School - Mohammad Reza Roozbeh (Journal of Global Pharma Technology, 2018)
The aura is one of the desired principles of new criticism school. It can be known as a quality that the art works should have. According to a special place that Hafez’ poetry has found in the mind and language of world, it is considered as one of the outstanding examples for studying the aura element. Since it is essential for Mission of the school of new criticism not to understand the quiddity of aura but how to be created it in a work of art, in this literary investigation we have studied the features that create the aura in Hafiz’ poetry; we examined the factors that cause these features and introduce each of these factors with some examples. The other achievement of this article is to explain the linguistic structures and intellectual factors that generate the aura of Hafez’ poetry.Keywords: New criticism, Luminosity, Linguistic constituents, Intellectual themes.